2020
DOI: 10.1029/2019ea000945
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Data Assimilation Techniques for Dynamical Downscaling of the Structure and Intensity of Tropical Cyclones

Abstract: The dynamical downscaling technique is used for the understanding of physical mechanisms associated with the atmospheric phenomena. We have developed high‐resolution analysis (6 km) for three tropical cyclones (TCs), namely, Phailin (2013), Nilofar (2014), and Chapala (2015) originated over the North Indian Ocean using the dynamical downscaling approach. The study aimed at the identification of appropriate methodology for generating analysis so that it becomes useful for identifying the role of environmental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Various foreign authors agree that giving a higher weight to the ensemble BEC, because theoretically its better represents the error of the day, leads to more realistic solutions [10] [11]. A similar result was obtained by Zhu et al [12], who estimated that a much higher weight for the ensemble covariance in a hybrid covariance, helps the proposed assimilation system to produce a more reasonable analysis field.…”
Section: Introductionsupporting
confidence: 66%
“…Various foreign authors agree that giving a higher weight to the ensemble BEC, because theoretically its better represents the error of the day, leads to more realistic solutions [10] [11]. A similar result was obtained by Zhu et al [12], who estimated that a much higher weight for the ensemble covariance in a hybrid covariance, helps the proposed assimilation system to produce a more reasonable analysis field.…”
Section: Introductionsupporting
confidence: 66%
“…Maintaining such networks to enable climate relevant over time will provide data with greatly improved spatial resolution to complement the network of fixed observation platforms. Improving representation of TC and ETC systems within global atmospheric reanalyses with more data assimilation ( 63 , 64 ) and development of new globally downscaled atmospheric reanalysis data ( 65 ) would also help to further constrain uncertainties. Expanding the limited number of dynamical global wave simulations forced by high-resolution downscaled climate models (0.25° or less) that are more capable of resolving TC-driven waves (relative to coarse CMIP-driven global wave simulations) ( 53 , 54 ) might also help to understand and reduce uncertainties in ETC and TC areas.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the internal dynamics on TC intensification and structural changes revealed that hybrid data assimilation techniques improved the overall quality of prediction compared to individual data assimilation methods (Malakar et al., 2020). A flow‐dependent sequential assimilation‐based targeted observation using the ensemble Kalman filter could minimize the analysis variance (Wu et al., 2020).…”
Section: Related Workmentioning
confidence: 99%